PENERAPAN METODE TALKING STICK UNTUK MENINGKATKAN KREATIVITAS BERPIKIR SISWA DALAM PENDIDIKAN AGAMA ISLAM SISWA KELAS V SDN 125 PEKANBARU - Siti Khadijah (Sosial Budaya, 2015)
This was an action research class. Based on observations in SDN 125 Pekanbaru, met some phenomena about the problem of low student creative thinking, such as: 1) during the learning process, only a few students who take active part, as seen from the lack of students asking questions or opinions on the teacher. 2) students seem difficult to understand the material presented by teachers in the classroom, it is seen that more than 65% of students can not answer questions put by the teacher. 3) when answering questions from teachers, other students respond with answers similar to students who have been answered before, and 4) in answering questions from teachers, students just transfixed by what they read without any attempt to develop a sentence, or use own words without changing the meaning of the answer. to overcome the lack of creativity these students think the author talking stick method to enhance student creativity thinking. Formulation of the problem for this study are: how to applied talking stick to increase the creativity to think of students in Islamic religious education in elementary school fifth grade students SDN 125 Pekanbaru?This research was conducted in two cycles, the data described is prior to action, in the first cycle and second cycle, each cycle is done in two meetings. In order to study this class action work well without the barriers that interfere with the smoothness of the study, researchers set stages in the research stage through which the class action, namely: 1) planning / preparation for action, 2) implementation of the action, 3) observation and reflection. Based on the results of observation before the measure of creativity to think of students obtained 44% with the low category. Then based on the observation in the first cycle indicates that the level of creativity to think of students reached by 64,8% with the high category. While on the second cycle there was an increase to reach the creativity to think of students obtained 84,0% with very high category.